2014
DOI: 10.5194/angeo-32-1145-2014
|View full text |Cite
|
Sign up to set email alerts
|

Ionospheric shock waves triggered by rockets

Abstract: Abstract. This paper presents a two-dimensional structure of the shock wave signatures in ionospheric electron density resulting from a rocket transit using the rate of change of the total electron content (TEC) derived from ground-based GPS receivers around Japan and Taiwan for the first time. From the TEC maps constructed for the 2009 North Korea (NK) Taepodong-2 and 2013 South Korea (SK) Korea Space Launch Vehicle-II (KSLV-II) rocket launches, features of the V-shaped shock wave fronts in TEC perturbations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 28 publications
5
44
0
1
Order By: Relevance
“…The phase velocities of this disturbances were 1.8-2.6 km s −1 , which is larger than the velocity of acoustic waves reported in previous studies. Lin et al (2014) observed also V-shaped TEC perturbations with periods of 100-600 s and velocities between 800-1200 m s −1 for the 2009 North Korea's Taepodong-2 and 2013 South Korea's Korea Space Launch Vehicle-II rocket launches. These disturbances were attributed to shock waves generated by the rocket's propulsive blasts.…”
Section: Introductionmentioning
confidence: 80%
“…The phase velocities of this disturbances were 1.8-2.6 km s −1 , which is larger than the velocity of acoustic waves reported in previous studies. Lin et al (2014) observed also V-shaped TEC perturbations with periods of 100-600 s and velocities between 800-1200 m s −1 for the 2009 North Korea's Taepodong-2 and 2013 South Korea's Korea Space Launch Vehicle-II rocket launches. These disturbances were attributed to shock waves generated by the rocket's propulsive blasts.…”
Section: Introductionmentioning
confidence: 80%
“…The general features of the rocket triggered ionosphere disturbances generated by 2016 North Korea rocket launch with the southward trajectory are qualitatively similar to the disturbances generated by 2009 North Korea rocket launch with the eastward trajectory as reported in Lin et al . []. Model simulations applying energy exerted by exhaust plumes nicely reproduce these disturbance wave features in time rate change of ionospheric electron density qualitatively.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there are numerous rocket launches around Asia regions providing opportunities for studying the ionospheric disturbances and waves triggered by rocket transits [e.g., Ozeki and Heki , ; Lin et al ., , ; Kakinami et al ., ; Ding et al ., ]. Using the two‐dimensional TEC maps constructed by ground‐based GPS receiver networks, Kakinami et al .…”
Section: Introductionmentioning
confidence: 99%
“…The initial parameters at 15:00 UT of the second day are then used to initialize the SAMI3/ESF. Nevertheless, these impulsive waves displaying a nonlinear wave pattern (N-shape) in vertical TEC profiles (not shown) are likely associated with the shock waves (e.g., Astafyeva et al, 2013;Zettergren et al, 2017), which are commonly observed during the rocket ascending (e.g., Afraimovich et al, 2002;Chou et al, 2018;Ding et al, 2014;Kakinami et al, 2013;Lin et al, 2014;. The longitude is limited to 6°with periodic boundary conditions for computing the potential and is centered at 3°so the universal time and local time are the same.…”
Section: Sami3/esf Modelmentioning
confidence: 99%